The contribution of residential situations to mental health during COVID-19: A longitudinal survey - Pablo García de Paredes; Sergio Cortez Ghio; Marie Baron; Annie LeBlanc; Carole Després (Wellbeing, Space and Society)
During the early stages of the COVID-19 pandemic, extended periods of confinement made housing the focal point of daily life. While the impact of sanitary health measures on mental health has been extensively studied, the role of housing remains less understood. Our literature review indicates that housing characteristics and usage patterns influenced mental health outcomes during the pandemic. This study aims to test the hypothesis that the concept of residential situation –an original framework integrating housing attributes, individual and household characteristics, and occupational profiles– is associated with stress, wellbeing, depression, and anxiety measures. We employed data mining techniques and ordinal logistic regression models on a sample of 781 participants from a longitudinal survey conducted in Québec, Canada, between April 2020 and May 2021. Our findings reveal that higher dwelling occupation density is positively associated with increased stress levels. Additionally, apartment living, after adjusting for the number of children under the age of nine, shows a significant association with stress. Feelings of depression and low wellbeing are linked with experiencing separation from loved ones. Also, depression, wellbeing, and anxiety measures were found to be strongly associated with income. This study underscores the effectiveness of a comprehensive framework, applying the interdisciplinary concept of residential situations to capture the nuanced impact of housing on mental health through its links to family dynamics, and shows the importance of social class membership for mental health during crises.